An Inverse Method for the Design of Structures - Limache, Alejandro Cesar (2008)
Inverse methods are powerful design tools that allow engineers to obtain efficient designs at much lower costs than the ones normally involved in experimental and direct computational design. Here we present an inverse method which allows the efficient design of deformable structures or components, such for example airplane wings. The inverse method proposed here allows the engineers to obtain the actual unloaded geometry they should request to a manufacture department, so as to obtain a structure or piece that under the work loads will deform to a pre-specified ideal shape. In the case of an airplane wing or an airfoil, for example, the engineer will be able to obtain the undeformed geometry of the wing such when it is flying at cruise speed subject to the aerodynamics loads, the wing will naturally deform to a pre-specified (and aerodynamically desired) shape. The presented inverse method is based on a novel formulation builded in terms of the finite element method.